Durability of shuttlecock - Tan, See Kian (Nanyang Technological University, 2023)
Badminton is a common competitive and recreational sports that is played around the world. In the market currently, shuttlecocks has split into two different types as compared to the older times. We now have both feathered shuttlecocks, which are usually made from bird feathers as well as synthetics shuttlecocks, which are made of plastic or nylon material. The characteristics that each type of shuttlecock possesses are different as well, feathered shuttlecocks provides higher aerodynamic performance while the synthetics shuttlecocks are more durable [1]. As technology progresses with time, we are looking into another type of shuttlecock, namely the chemically treated shuttlecocks. In turn, this would provide both aerodynamic performances as well as increasing the durability of the feathered shuttlecocks. With better technology progression, testing methods on the durability of shuttlecock can also be further improved along with new testing criteria. The aim of this Final Year Project (FYP) is to look into the durability of various Badminton World Federation (BWF) approved feathered shuttlecocks as well as chemically treated shuttlecocks. This is an project that builds on the previous FYP Project done in Year 2021/2022, where the following shuttlecocks: Lining A+300, AeroplaneEG1130, RSL Tourney Classic, Yonex AS50, Victor Gold 1, Ashaway Official, Chemical-Treated A and Chemical-Treated B were put into test for its durability. Whereas in the current FYP experiment, another set of 4 BWF approved shuttlecocks and 3 chemically treated shuttlecocck were subjected to a series of durability test, the shuttlecocks are namely: Yonex AS09, Yonex AS30, Yonex AS60, RSL Supreme, Durabird AS40, Durabird AS60 and Durabird AS90. The shuttlecocks in this experiment went through a series of durability test using the Shuttlecock Launcher where the badminton racket propels at a velocity of 35.34m/s. At every 10 hits, the deformation of the each shuttlecock were recorded and every shuttlecock went through a total of 90 hits. This testing method is a modified version of the durability test that is done by BWF where they have professional players to smash the shuttlecocks for 10 strokes progressively. Photograph of the damage of each shuttlecocks at Hit 0 all the way to Hit 90 were documented.